Brexit and the European Shape of Things to Come - Hunter, Fiona; de Wit, Hans (International Higher Education, 2016)
Brexit has happened and it will have far-reaching consequences both for UK universities and the further development of the European Higher Education Area. In a relatively short period of 15 years, European integration has gone from a forward-looking process of integration to an increasingly more complex and challenging endeavour of dealing with diversity in its various manifestations. In the grips of an economic and political crisis, and with a massive refugee emergency unfolding along the European borders, the integration process is falling apart. The spirit of cooperation has diminished as European institutions have not been able to present credible solutions to the problems faced. Anti-European Union sentiment is spreading among its member states, with Brexit its most manifest outcome so far. Higher education has appeared to be immune to these trends with the Bologna Process, the research program Horizon 2020 and the education program ERASMUS+ as clear manifestations of increased co-operation and funding. However, Brexit has it made clear that European Higher Education, despite its commitment to regional co-operation, cannot escape the changing reality around it. Greater intentionality and integration of internationalisation into institutional mission can enable UK universities to demonstrate the value and impact of an international community of students and scholars, firstly to themselves and secondly to the Government in the upcoming negotiations.